Evaluation of A Better Approach for Open Reduction Of Severe Gartland Type III Supracondylar Humeral Fracture. Issue 5 (28th May 2021) - Su, Yuxi; Nan, Guoxin
Abstract: Background: An optimal surgical approach is required to treat Gartland type III supracondylar humerus fractures (SHFs) in children when open reduction is inevitable, especially in patients with neurovascular injuries. The purposes of this study were to find a better approach for open reduction of Gartland type III SHFs and to achieve anatomic reduction, stable fixation, and good functional and cosmetic outcomes with this approach. Methods: This retrospective study was performed in our hospital between January 2008 and June 2014. After the exclusion criteria were applied, 91 children were treated with the mini-anterior approach for severe Gartland type III SHFs. A 2–3-cm long anterior incision was made radially along the anterior transverse groove of the elbow, through which the nerve and vessel were probed, if necessary, and fracture reduction and Kirschner (K)-wire insertion were performed. Radiological evaluation included the Baumann angle and carrying angle. The functional and cosmetic evaluation was based on range-of-motion measurements and the criteria defined by Flynn. Chi-square and independent t tests were used for the statistical analyses. Results: Thirty-two patients were impossible to reduce, 1 patient had brachial artery injury, 37 patients had a sign with compartmental syndrome, 6 patients had open fractures, and 15 patients had multiple trauma. The interval between injury and hospitalization was 1 hour to 12 days. Overall, 91 patients were followed for 12 months to 4 years (average, 26.5 months). All incisions were healed by primary intervention. The fracture healing time was 3–5 weeks (average, 3.8 weeks). Elbow function recovered after 3 months, without obvious cubitus varus. Postoperative radial nerve paralysis occurred in 2 patients and healed within 2 months. Postoperative ulnar nerve paralysis occurred in 2 patients, and one of the K-wires was removed after 1 day. Nerve injuries were relieved within 3 months for both patients. The outcomes, according to the Flynn criteria, were excellent in 73 patients, good in 12 patients, and fair in 6 patients. The rate of excellent and good outcomes was 93.41%. Conclusions: The advantages of the mini-anterior approach include minimal trauma, simple and rapid exposure, easy tissue repair, and possibility of probing and repairing nerves, vessels, and muscles. It is an optimal surgical approach for the treatment of Gartland type III SHFs when open reduction is inevitable, especially in patients with neurovascular injuries.